(untitled) (Journal of the College of Education for Women, 2019)
Human resources are considered as strategic fortune for being the main driver of the development wheel in the society, and the field of education and learning is one of the main pillars of this fortune for its great effect in the process of economic and social progress of individuals. I was the subject of education to the concerns of many countries, as adopted national policies . And regional support and the reduction of constraints, so came our study (education hub for human development) to identify the role of education in human development and to identify the obstacles facing the education process and the extent of its impacts negatively on the process of human development also contribute to the knowledge of school enrollment and the extent of its impact on human development, and work to provide the necessary needs and requirements to raise the educational services. And gaining the study of great significance because education is one of the cornerstones of human development, it is also among the important pillars to build a knowledge-based society, it means actors to fight poverty, ignorance and extremism and the reduction of social crises and unrest political and security stability and security as it manifests the importance of this study addressed the phenomenon of development, which means the development of human society, because man is a tool and a very economic development in all its dimensions and political and social classes and trends intellectual, scientific and cultural. The search includes two sections have reached an outcome of the most important: 1 - The results of the study showed that education leads to raise the level of public services in the community. 2 - Results showed that the ratios of non-enrollment of children covered by the compulsory education in schools is very high for both sexes due to the bad security situation and the distance between the home and the school has had a negative effect in the failure of the sons to continue the education process 3 - found that double shifts school and after school buildings and geographical location another reason not to pursue the sons of Education 4 - The results of the study show that literacy helps to achieve material well-being of the community. Also came out ofthe most important recommendations : Cooperation with the civil society institutions through central and sectoral symposiums for all the parties of the education process and the inhabitants, especially in the areas where schools suffer from high leakage rates, and the adoption of successful methods to address these cases. 2. There is a need to take care of schools buildings, and the availability of basic services in these buildings through the preparation of a map of spatial distribution of schools buildings within the city of Baghdad using the (GIS) system in agreement with the Ministry of Education, Directorates of Education, and Baghdad Mayoralty. The map must include locations of the educational institutions in all the districts of the city of Baghdad to be the base of all the decisions related to construction, maintenance and repair of these buildings, and prepare schedules for periodic visits to all schools in the area to determine their needs for maintenance and sustainability. 3. Increasing the attention to the late students, through the provision of programs for the orientation and educational guidance and opening schools in Iraq for adult education. 4. Improving the educational level in the country, by enriching the curriculums and teaching methods and raising the level of teachers, which hinder the education process. 5. The provision of health services in each school to improve the health of students and children.